Impact of proactively inviting people with advanced cancer to talk about the end of life: a randomised clinical trial protocol - Albert Balaguer; Iris Crespo; Cristina Monforte-Royo; Joaquim Julià-Torras; Aina García-Salanova; María Jimeno Ariztia (BMJ Open, 2025)
Introduction There is evidence that talking about the end of life with patients facing a life-threatening disease is not upsetting, and in fact, it may even be beneficial. However, both patients and health professionals can find it difficult to engage in these conversations. The aim of this clinical trial is to explore whether proactively inviting people with advanced cancer to share their thoughts about death and dying is distressing for them, comparing the impact with usual clinical practice (ie, a reactive approach to these issues).Methods and analysis A stepped-wedge cluster randomised controlled trial involving six palliative care units in Spain will be conducted. Each unit will recruit participants for both the experimental and control groups. Units will be randomised to determine the order in which they will begin implementing the intervention: GO-TaD (Give the Opportunity to Talk about Death thoughts). The trial will involve six sequences and seven periods (steps), with four patients per period (patients in each period will be different). The primary outcome will be emotional distress, assessed with the Detecting Emotional Distress scale. The following secondary variables will also be analysed: hopelessness, using the Beck Hopelessness Scale; quality of the patient–professional relationship, with the Patient–Doctor Relationship Questionnaire (PDRQ-9); and quality of life, with the Palliative Outcome Scale . The trial will follow the CONSORT extension for stepped-wedge cluster randomised designs. The primary analysis will include all eligible patients, applying mixed-effects regression models for binary results and mixed linear models for continuous data. Results will be reported as risk differences and ORs, with 95% confidence intervals. Analyses by sub-groups of interest (eg, age, gender, type of palliative care unit) will also be conducted. All analyses will be performed using R.Ethics and dissemination Ethical approval has been obtained from the researchers' university and all participating centres. Results will be disseminated through peer-reviewed open access publications, academic conferences and presentations to clinical audiences.Trial registration number NCT06420609.